Cloud Storage Access Control Scheme of Ciphertext Algorithm Based on Digital Envelope. Issue 2 (2nd April 2016) - Xiong, Anping; Xu, Chunxiang
Abstract: Ciphertext Policy Attribute-Based Encryption (CP-ABE) has been widely studied in recent years because it is more suitable for access control of shared data under cloud storage environment. In view of problems of flexibility and efficiency of the existing encryption schemes under cloud storage environment, combined with digital envelopes technology, the paper puts forward an optimized scheme based on supporting fine-grained access control. The scheme has the following advantages: Adopting digital envelopes technology, reducing the computational overhead of Data Owner significantly on the basis of the ensuring data confidentiality, using proxy re-encryption technology to realize the support of user and attribute revocation flexibly, furthermore, the backward and forward secrecy also have been ensured. Adopting security protocols to distribute the shared keys between users and cloud storage server, cloud storage server can save the overhead in maintenance of a large user key's tree. Security and performance analysis show that Cloud storage access control scheme of ciphertext algorithm based on digital envelope can ensure the confidentiality of data, resist collusion attack with forward and backward security, and also reduce the calculation works of the user owners and accessing users.